Cross-cultural adaptation and measurement properties of the VISA-A questionnaire for Chinese patients with Achilles Tendinopathy. (November 2021) - Chang, Rui; Tsang, Raymond Chi-Chung; Jiang, Dong; Liu, Dongsen; Ruan, Bin; Lin, Guohui; Liu, Chunlong; Gao, Qi
Abstract: Objective: To culturally adapt the VISA-A into a simplified Chinese version (VISA-A-CHN) and test its measurement properties. Design: Methodological study; Setting: Hospital and university laboratory. Participants: 240 subjects were divided into the healthy (n = 80), at-risk (n = 80), and tendinopathy groups (n = 80). Main outcomes measures: The internal consistency, test-retest reliability, construct validity, and the floor and ceiling effect of the VISA-A-CHN. Results: The VISA-A-CHN showed adequate internal consistency (Cronbach's α = 0.73, 95% CI 0.63 to 0.81), excellent test-retest reliability (ICC3A, 1 = 0.97, 95%CI = 0.95 to 0.98), standard error of measurement of 2.2 points, minimum detectable change of 6.0 points, with no floor and ceiling effects. Two factors (pain/symptoms and physical function/activity) were extracted in exploratory factor analysis. There were moderate associations of VISA-A-CHN score with scores of Lower Extremity Functional Scale and SF-36 physical components ( r s = 0.53–0.74, P < 0.01) but low associations with SF-36 mental components ( r s = 0.12–0.22, P > 0.05). VISA-A-CHN mean score of Achilles tendinopathy group was significantly lower than those of healthy and at-risk groups (P < 0.01). Conclusions: The VISA-A-CHN is equivalent to the original version in terms of language and measurement properties. It can be used as the outcome measure for Chinese patients with Achilles tendinopathy. Highlights: The VISA-A has been culturally adapted from English into Chinese. The Chinese version of the VISA-A shows acceptable reliability and validity. The VISA-A-CHN can be used to assess the severity of Chinese patients with AT.